The Effect Of Jicama Flour Substitution On The Quality Of Cupcake - Putri, Suci Fortuna; Gusnita, Wiwik (Universitas Negeri Padang, 2022)
This research is motivated by the use of local food ingredients, namely jicama which is still lacking. Jicama is used as flour to be varied into cupcakes. The purpose of the study was to analyze the effect of 0%, 25%, 50% and 75% substitution of jicama flour on the quality of cupcakes in terms of volume, shape, color, aroma, texture and taste. This type of research is a pure experiment with a completely randomized design method (CRD) and three repetitions. Sources of data in this study were obtained from 3 expert panelists, namely lecturers from the Department of Family Welfare, Concentration of Catering Education, Faculty of Tourism and Hospitality, Padang State University. The tool used to collect data is in the form of a questionnaire containing questions about the quality of the cupcakes. The data were analyzed using ANOVA, if Fcount≥Ftable then continued with Duncan's Test. The results showed that there was a significant effect of substitution of jicama flour between 0%, 25%, 50% and 75% on the quality of the cupcake, namely the quality of the golden yellow color, the aroma of the jicama-flavored cupcake, the overall sweetness and the taste of jicama. The quality of expanding volume, shape (neat, uniform and tubular), fragrant aroma and soft texture have no effect on the quality of the cupcake. The result of the best quality test of jicama flour cupcake is in X1 treatment with 25% jicama flour substitution.